90 years young (Raton Range Raton, New Mexico, 1988)
Newspaper Article on the 90th birthday of Florence Brown.
Master list item #: 30
File location is in the Raton File Cabinet
Keywords: Brown, Florence; Brown, Trigg; Brown, Ralph; Graham, Trella; Holiday Inn; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico